Dimensioning of longitudinal reinforcementsin concrete beams with a non-rectangular section and variable height - Diaz Huedo, J.I.=700 1 Montero Martinez, J.; Galletero Montero, P.
(Es, En)
ilus., 10 ref.
Keywords: CONSTRUCCIONES; HORMIGON; ALOJAMIENTO DE ANIMALES; ESPAÑA; DIAGRAMA DE INTERACCION